HE EFFECT OF TECHNOLOGY ACCEPTANCE MODEL, PERCEIVED TRUST, SECURITY, AND ATTITUDE TOWARD OVO USAGE - Malonda, Ryan Ch.; Tulung, Joy E.; Arie, Fitty F. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Technologies are affecting a lot of things one of them is digital money. In Indonesia one of the most popular E-payment platforms is Mobile wallet. There are several mobile wallets that are already launched in Indonesia and one of them is OVO. With all the benefits, there are still people who still more comfortable in using physical money. The research purpose is to find out the effect of technology acceptance model, perceived trust, security, and attitude toward the usage of e-payment which in this case is OVO. The research is taken from 100 respondents that are using OVO. To analyze the data, this research is using several tests such as research instrument test, Classical assumption, classic hypothesis test, and multiple regression analysis. From the result of the test it shows that usefulness, ease of use, trust, and security are not significant to Usage of OVO both simultaneously and independently. But, attitude is significantly affecting OVO usage. it is recommended for OVO to find another way to attract new users. OVO may keep using promotion to attract customer. But, the company cannot keep using the same strategy. OVO may try to change their reward system from OVO points to using cashback.Keyword: marketing, e-payment, usage